Heat release rate of high-speed train fire in railway tunnels. (November 2020) - Zhou, Yuanlong; Wang, Honglin; Bi, Haiquan; Liu, Xiaoxia; Gou, Qilin
Highlights: Study the impact factors on the heat release rate of the high-speed train fires. A higher power of the fire source corresponds to an earlier PHRR of the train fire. The PHRR of high-speed train is 33.6–36.4 MW. The PHRR of high-speed train increased as the area of train carriage vents increased. The PHRR of high-speed train decreased as the ventilation velocity increased. Abstract: In this study, a cone calorimeter and an ignition temperature tester were used to conduct experiments on the combustible materials of the main structure of a train for determining its heat release rate and ignition temperature. According to the experimental data of the materials, a numerical model for high-speed train fires was established, and it was validated on the basis of full-scale train fire experiments reported in the literature. Numerical calculations were performed to study the effects of the area of the train carriage vents, power of the fire source, position of the fire source, and longitudinal ventilation velocity of the tunnel on the heat release rate. The results indicated that a higher power of the fire source corresponds to an earlier peak of the heat release rate of the train fire. When the fire source was set at the end wall corner of the carriage and the fire source power was 150–1000 kW, the peak heat release rate was 33.6–36.4 MW. The peak heat release rate of high-speed train fires has an exponential relationship with the area of the train carriage vents and an exponential decay relationship with the longitudinal ventilation velocity of the tunnel. When the fire source is below a seat and its power is low, the flame height is so small that the temperature of the smoke at the top of the train carriage is lower than the ignition temperature of the ceiling material. Hence, the ceiling material does not burn, and it is difficult for the fire to spread in the carriage. The flame spread characteristics of the fire are similar when the source is at other positions. The flame spreads along the ceiling to the two ends of the carriage, causing the seat and floor to burn owing to the heat radiation from the ceiling.